MEANING OF SIGN IN IPHONE 15 PRO (ON WITH THE SHOW) ADVERTISEMENT: ROLAND BARTHES APPROACH - Abidah, Nabila Farah; Neisyiah, Devana Nur; Afifuddin, Muzakki; Aisyah, Rasyidah Nur; Zamroni, Mohammad (Program Studi Bahasa Inggris, Universitas Panca Marga, 2024)
This study investigates the meaning of the symbols displayed in the iPhone 15 Pro